2021
DOI: 10.3389/fpubh.2021.733519
|View full text |Cite
|
Sign up to set email alerts
|

The Populations' Resilience Toward the Policymaking Discrepancies in the Pandemic Covid-19 Period

Abstract: The world is in the midst of a crisis unlike any other in recent memory. COVID-19 is a pandemic that is urgent, global in scope, and has huge consequences. The policy sciences provide insights into unfolding trends, and this article uses the lessons of the literature to better understanding the policymaking shifts and population acceptability of COVID-19. The author attempts to investigate how policymakers' emotions and narratives affect policy decisions and form policymaker-population relationships. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The effectiveness of control and mitigation strategies such as the closure of nonessential businesses and services, is debated [4,5]. Additionally, while some studies showed that, at least in the pre-Omicron phase, school closures were associated with a decrease in COVID-19 incidence and mortality [6], other studies concluded the contrary [7].…”
Section: Of 13mentioning
confidence: 99%
“…The effectiveness of control and mitigation strategies such as the closure of nonessential businesses and services, is debated [4,5]. Additionally, while some studies showed that, at least in the pre-Omicron phase, school closures were associated with a decrease in COVID-19 incidence and mortality [6], other studies concluded the contrary [7].…”
Section: Of 13mentioning
confidence: 99%